DNA polymerase η mutational signatures are found in a variety of different types of cancer - Rogozin, Igor B; Goncearenco, Alexander; Lada, Artem G; De, Subhajyoti; Yurchenko, Vyacheslav; Nudelman, German; Panchenko, Anna R; Cooper, David N; Pavlov, Youri I (Cell cycle (Georgetown, Tex.), 2018)
DNA polymerase (pol) η is a specialized error-prone polymerase with at least two quite different and contrasting cellular roles: to mitigate the genetic consequences of solar UV irradiation, and promote somatic hypermutation in the variable regions of immunoglobulin genes. Misregulation and mistargeting of pol η can compromise genome integrity. We explored whether the mutational signature of pol η could be found in datasets of human somatic mutations derived from normal and cancer cells. A substantial excess of single and tandem somatic mutations within known pol η mutable motifs was noted in skin cancer as well as in many other types of human cancer, suggesting that somatic mutations in A:T bases generated by DNA polymerase η are a common feature of tumorigenesis. Another peculiarity of pol ηmutational signatures, mutations in YCG motifs, led us to speculate that error-prone DNA synthesis opposite methylated CpG dinucleotides by misregulated pol η in tumors might constitute an additional mechanism of cytosine demethylation in this hypermutable dinucleotide.
Keywords: Exome; mutable motif; DNA lesion bypass; skin cancer; DNA-Directed DNA Polymerase; Skin Neoplasms; sloppy DNA polymerase; regulace genové exprese u nádorů; exom; mutace; Neoplasms; Base Sequence; sekvence nukleotidů; Hypermutation; Mutation; Humans; Gene Expression Regulation, Neoplastic; nádory kůže; nádory; Skin; POLH; gene expression profiles; DNA-dependentní DNA-polymerasy; kůže; lidé